The modular system is a kind of method to increase students qualities in descriptive geometry during process of study - Krasnyuk, A. V.; Tatiana, T. V. (Science and Transport Progress, 2011)
The comparison of classical and computer testing system is given in the article. The effect of usage of «Prometey» remote education system is analyzed. The positive effects of passing the Module Tests by students are shown.